Problem-based learning on doctoral level: fit for ‘pracademics’? (Journal of Universal Excellence, 2026)
Research Question (RQ): To what extent could problem-based learning (PBL) have a potential role on doctoral programmes as an activating learning approach for overcoming mid and late career doctorate candidates’ challenges?Purpose: The purpose of the paper was to firstly explore challenges of experienced working professionals in doctoral education. Secondly, the existing models of problem-based learning (PBL) as practiced in the four original Universities first to employ PBL, were comparatively examined in order to assess the potential role of PBL in overcoming mid and late career doctoral candidates’ challenges.Method: Through engaging with the peer-reviewed journal articles and publicly available Canadian, Dutch, and Danish universities’ documents on PBL, an analysis of well-researched and documented advantages and challenges of so-called ‘pracademics’ (practitioners entering academia) were carried out followed by a comparative analysis of diverse PBL models. In the end, interconnections between pracademics’ challenges and PBL features and procedures were identified.Results: Five challenges that mid and late career doctorate candidates face regularly have been identified including their struggle with grasping Threshold Concepts in learning to be a researcher. Others involve passive learning environment, prior professional knowledge being undervalued, fear of failure as well as knowing the answer in advance due to over-eagerness to solve problems through their research and overreliance on professional experience. Comparative analysis of different PBL models featured some differences in problem types (practice-oriented, content-oriented and critique-oriented), teachers’ role (facilitator, tutor and supervisor) and educational processes and principles. Most of the PBL features could be instrumental in aiding pracademics in overcoming their challenges in doctoral education such as, for example, small group project work facilitating better understanding of Threshold Concepts as well as minimising ‘knowing the answer in advance’ attitude – to name just a few.Organization: Not only higher education organisations but also other public or private sector organisations could benefit both from identifying their mid and late career employees’ challenges and from employing problem-based learning approach for further development of individuals, groups and teams.Society: The contribution to society is reflected in the inclusion strategies of more mature candidates in doctoral education thus contributing to a cycle of lifelong learning.Originality: The paper contributes to understanding of newly emerged type of doctoral candidates – pracademics – through visual mapping of interconnection between their challenges and the PBL features and procedures.  Limitations / further research: The paper’s scope was limited as it focused only on the four original Universities that have been applying PBL for the last 50 years. Also, studies on the use of PBL on doctoral level are still rare that consequently led to limited access to concrete examples.
Keywords: problem-based learning; activating learning approach; mature doctoral candidates; pracademics; threshold concepts